Breast Stroke Swimming Ability in Students Interested in Swimming Sports Talent - Ellya Putri, Nafala Regita; Jariono, Gatot; Sistiasih, Vera Septi (Universitas PGRI Palembang, 2025)
This study aims to analyze the level of breast stroke swimming ability in students of the Swimming Talent Interest of the Muhammadiyah University of Surakarta. The method used is descriptive research with a quantitative approach, involving 20 students as samples. Data were obtained through swimming ability tests and analyzed using descriptive statistical techniques. The results showed that the majority of students had appropriate abilities in breast stroke swimming techniques , with the highest percentage in the appropriateness of body position when gliding (75%). However, there were also some students who still needed improvement in leg movement techniques, hand movement techniques, breathing techniques, and movement coordination techniques. The conclusion of this study is that although most students showed good abilities, there is still a need for additional training to improve their swimming skills.